ANALISIS YURIDIS PENJATUHAN PIDANA DI BAWAH MINIMUM KHUSUS TERHADAP TINDAK PIDANA NARKOTIKA (Studi Kasus Putusan Nomor 42/Pid.Sus/2019/PN Bpd) - Alex Firdaus Simaremare; Lu Sudirman; Elza Syarief (Legal Standing : Jurnal Ilmu Hukum, 2023)
One of the products of non-codified criminal regulations that adheres to a special minimum system. Article 12 paragraph (2) of the Criminal Code specifies the minimum criminal penalties applicable in Indonesia for one day of imprisonment, while Article 18 paragraph (1) of the Criminal Code also specifies one day of imprisonment as the minimum sentence for imprisonment. This is typically the case. However, the Criminal Code does not regulate the specific minimum criminal hazard level. Article 103 of the Criminal Code states that laws outside the Criminal Code can regulate special rules; in this case, based on the District Court Decision Number: 42 / Pid.Sus / 2019 PN Bpd, the defendant Syamsul Rizal Bin Zainal was sentenced in accordance with the subsidiary charges of the Public Prosecutor article 111 paragraph 1 with a minimum criminal threat of 4 years and a fine of Rp. 800,000,000 (Eight Hundred Million RupeesIn this legal research, a legal approach, a conceptual approach, and a case approach will be utilized, along with specific research requirements. In this investigation, both primary and secondary legal materials were utilized. The analyzed legal material is presented in a methodical, logical, and reasonable manner. On the basis of the study's findings, it is possible to conclude that the criminal conviction below the specified minimum in decision number 42/Pid.Sus/2019/PN Bpd violates the principle of legality (nulla poena sine lege), as the decision lacks legal considerations.